2013
DOI: 10.1007/s13205-013-0116-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Libyan date palm resources by microsatellite markers

Abstract: Molecular typing of 377 female date palm trees belonging to 18 Libyan cultivars and representing common genotypes in the central Libyan oasis of Al Jufrah was performed using 16 highly polymorphic microsatellite or SSR loci. A total of 110 alleles with an average of 6.88 alleles per locus were scored indicating the high level of polymorphism existing among the cultivars thus allowing their genetic fingerprinting. Moreover 28 alleles out of 110 were fixed. All the cultivars were characterized by negative values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
3
32
0
1
Order By: Relevance
“…2.3.1 ). Apparently, there is little information available about the status of these species in the wild; their habitats are in many cases threatened by multiple anthropogenic and environmental factors (Chao and Krueger 2007 ;Munier 1981 ;Popenoe 1913 ). In addition, most of these species are lacking characterization and evaluation as potential genetic resources, and it is highly likely that the diversity of some species is threatened by genetic erosion (Krueger 1998(Krueger , 2011.…”
Section: The Genus Phoenixmentioning
confidence: 99%
See 1 more Smart Citation
“…2.3.1 ). Apparently, there is little information available about the status of these species in the wild; their habitats are in many cases threatened by multiple anthropogenic and environmental factors (Chao and Krueger 2007 ;Munier 1981 ;Popenoe 1913 ). In addition, most of these species are lacking characterization and evaluation as potential genetic resources, and it is highly likely that the diversity of some species is threatened by genetic erosion (Krueger 1998(Krueger , 2011.…”
Section: The Genus Phoenixmentioning
confidence: 99%
“…Three wild Phoenix species grow on the fringes of traditional date palm cultivation in the Old World, and they may have enriched the gene pool of the cultivated species through spontaneous hybridization. These are P. atlantica which grows near the Atlantic shores of North Africa, and it is apparently involved in the formation of some Moroccan date palm cultivars; however, P. atlantica may represent only feral populations of P. dactylifera and may not be considered as a valid species (Popenoe 1913 ;Rivera et al 2008 ). Phoenix iberica is a wild species growing in wadis near the Mediterranean coast of Spain; it has glaucous leaves, stout stems, and small fruit with thin fl esh; its fruits are intermediate between P. theophrasti and P. sylvestris .…”
Section: The Genus Phoenixmentioning
confidence: 99%
“…Fixation index, but not population differentiation, was significantly correlated with total diversity (r = 0.65; p = 0.05); also expected, but not observed heterozygosity, was correlated with total diversity (r = 0.73; p = 0.05). A recent study was carried out (Racchi et al, 2013) for the molecular typing of 377 female date palm trees belonging to 18 cultivars from Libya using 16 highly polymorphic SSR loci. The study reported scoring a total of 110 alleles with a mean of 6.88 alleles per locus.…”
Section: Microsatellites (Ssrs)mentioning
confidence: 99%
“…Observed heterozygosity can be predicted by the following equation: However, a closer inspection f the data revealed a non-linear relationship between Ho and He ( Figure 5) Racchi et al (2013) genetically characterized Libyan date palm cultivars using SSR markers (Table 7). In this study, both He was found to be slightly larger than and significantly correlated (r = 0.79; p = 0.01) with Ho; however, both were positively correlated with number of genotypes found in the study.…”
Section: Heterozygositymentioning
confidence: 99%
“…It is cultivated in the Middle East and North Africa (Hamza et al, 2011), where it is considered a valuable fruit crop (Racchi et al, 2014). The annual global production of dates is estimated to be about 7.4 million tons, while Saudi Arabia accounts for more than one million tons (FAOSTAT, 2013).…”
Section: Introductionmentioning
confidence: 99%